2011
DOI: 10.5511/plantbiotechnology.10.1101b
|View full text |Cite
|
Sign up to set email alerts
|

Production of picotee-type flowers in Japanese gentian by CRES-T

Abstract: Chimeric repressor gene-silencing technology (CRES-T) is an efficient gene suppression system in a wide variety of dicots and monocots. In this study, we demonstrated that the CRES-T system functions in Japanese gentian. A chimeric repressor of the anthocyanin biosynthetic regulator gene GtMYB3, under the control of the Arabidopsis actin2 promoter, was introduced into blue-flowered gentian. Of 12 transgenic lines, 2 exhibited a picotee flower phenotype with a lack of pigmentation in the lower part of the petal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Chimeric repressor gene-silencing technology (CRES-T) has provided unique transgenic ornamental flowers (Nakatsuka et al 2011;Shikata et al 2011;Tanaka et al 2011). CRES-T is a type of dominant-negative strategy for transcription factors in which a transcription factor fused to a modified ERF-associated amphiphilic repression (EAR)-motif repression domain functions as a dominant chimeric repressor in transgenic plants, which leads to a loss-of-function phenotype even in the presence of redundant transcription factors (Hiratsu et al 2003).…”
mentioning
confidence: 99%
“…Chimeric repressor gene-silencing technology (CRES-T) has provided unique transgenic ornamental flowers (Nakatsuka et al 2011;Shikata et al 2011;Tanaka et al 2011). CRES-T is a type of dominant-negative strategy for transcription factors in which a transcription factor fused to a modified ERF-associated amphiphilic repression (EAR)-motif repression domain functions as a dominant chimeric repressor in transgenic plants, which leads to a loss-of-function phenotype even in the presence of redundant transcription factors (Hiratsu et al 2003).…”
mentioning
confidence: 99%
“…For example, colour modified petunia, torenia and gentian (reviewed by Nishihara and Nakatuska 2010 and morphologically modified torenia (Narumi et al 2008), cyclamen , gentian (Nakatsuka et al 2011), morning glory (Ono et al 2011Sage-Ono et al 2011) and rose (Gion et al 2011) have been developed. Insect resistant chrysanthemum (Shinoyama et al 2008) has also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The gtmyb3-1 to gtmyb3-4 alleles were characterized as inactive in transient expression and yeast twohybrid assays , data not shown). When a chimeric repressor of GtMYB3 was transformed into blue-flowered gentian, a white-centered picotee petal-color phenotype was observed, indicating that this gene was responsible for flower pigmentation in Japanese gentians (Nakatsuka et al 2011). First, we developed a co-dominant SCAR marker to distinguish gtmyb3-1 and gtmyb3-3 alleles, which have insertions of independent transposable elements in the second exon, from other GtMYB3 alleles (Figs.…”
Section: Discussionmentioning
confidence: 96%